Microfabrication technology for biochips - Lim, Wei Wen. (2013)
The purpose of this project is to firstly establish a bonding procedure for bonding of PDMS to aluminum surface, secondly to review the bonding procedure for bonding of PDMS to PCTE membrane and finally to design a microfiltration platform with use of acrylic instead of PDMS.